Clinical Effects on Skin Texture and Hydration of the Face Using Microbotox and Microhyaluronicacid - JongSeo Kim, MD (Plastic and Reconstructive Surgery, Global Open, 2018)
Background:. Improving skin texture in the face is a popular procedure in older women. Procedures using stabilized hyaluronic acid (S-HA) to improve skin texture should be distinguished from volumizing procedures. The intradermal injection of S-HA has many benefits, such as being safe from embolism, having a high ease of injection, and leading to dramatic improvements in skin texture and hydration. HA is the main component of the extracellular matrix and dermal hydration can help counteract the effects of aging. When the dermis is well hydrated using S-HA, it looks healthier, and this effect can last for more than half a year. Various intradermal injection techniques have been reported, such as manual injection, the blanching technique, and using an automatic injector with multiple needles. Method:. The dermis can be treated with microdroplets (0.001 cc) of S-HA at a thousand of injection sites using an injector. This unique injection method was Named "Microhyaluronicacid" by the author, based on an analogy with Microbotox5. The author invented a unique injection solution in which S-HA is mixed with botulinum toxin A; this solution has been used for dermal hydration and skin rejuvenation since 2009. To reduce the risk of creating a dermal lump, polydensified monophasic HA and automatic injector were used. Microhyaluronicacid and Microbotox were combined by the author. Results:. In 50 patients, changes in fine wrinkles were measured using a dermascope, and dermal hydration was measured by transepidermal water loss and stratum corneum hydration levels. Conclusion:. The changes of transepidermal water loss and stratum corneum hydration were statically significant at 4 and 8 weeks.